Pengembalian Kredit dalam Hal Meninggalnya Debitur pada Lembaga Perkreditan Desa (LPD) Buduk, Mengwi Kabupaten Badung - Ida Ayu Gede Putri Satrianingsih; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Jurnal Konstruksi Hukum, 2021)
Village Credit Institution is a financial institution located in the Pakraman village which was established based on regional regulations and local awig-awig. In credit repayment, there are some factors that cause credit cannot be returned by the debtor, one of which is when the debtor dies. The problems examined in this study are the factors that cause the debtor to be unable to return credit to the Buduk Village LPD, and how to return credit to the Buduk Village LPD in the event the debtor dies. The type of research used is the empirical legal research with sociological approach and the fact approach. The results illustrate that the factors that cause the debtor to be unable to return credit to the Buduk LPD are bankruptcy of the business, the debtor's payment ability, the debtor's health, the debtor's death. Then, the procedure of credit refund at the Buduk LPD, namely the amount of the loan or principal will be subject to loan rate from the principal amount paid by the debtor, if the debtor dies, the credit return is delegated to the heirs by submitting a death certificate first.